Heritage activation and tourism development in Saldungaray, Province of Buenos Aires: From «Tourist Village» to «Best Tourism Villages» (ONU) - Bonanno, Flavio Adrián (2025)
This article examines the process of heritage activation in Saldungaray (Buenos Aires Province, Argentina), which took place within the framework of the public program Pueblos Turísticos (2008-2023), aimed at promoting tourism development in non-urban areas of the region. The study analyses how the recovery and display of heritage elements mobilised emerging forms of social organisation and how these forged strategic alliances to transform a locality marginalised by industry into a developing destination recognised by the UN in the «Best Tourism Villages» competition. The empirical contribution of this work lies in the characterisation of the heritage activation process and in the ways certain local actors reinterpret the notion of development and the objectives proposed by the program, subordinating the State’s planner-promoter premises to a locally legitimised vision. From this perspective, the town’s international recognition is seen as a consequence that transcends the program’s original scope.